International Monetary Fund Annual Report 1954. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1954)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1954. The report highlights that downward trend in the volume of world trade that had appeared early in 1952 was reversed in 1953, and in the last three quarters of that year, the rate of both the volume and the value of world trade exceeded that of 1952. The pattern of recovery, moreover, was such that it eased substantially the balance-of-payments disequilibrium.